2011
DOI: 10.1080/ac.66.5.2131085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of restenosis rate with sirolimus-eluting stent i n STEMI patients with and without diabetes at 6-month angiographic follow-up

Abstract: The present study demonstrated that diabetes increased restenosis after sirolimus-eluting stent placement in STEMI patients. This finding implicates that diabetes remains an important predictor for restenosis in the DES era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…25 They were also found to have higher FIGURE 4 Multivariable analysis of restenosis and in -stent thrombosis predictors in patients with a history of percutaneous coronary intervention (PCI) who were referred for PCI on admission; A -predictors of in -stent thrombosis; B -predictors of restenosis Abbreviations: see conflicting results. [29][30][31][32] Similar results were described in patients with restenosis after carotid artery stenting. 33 One of the possible explanations is that smokers have a reduced sensitivity to restenosis, and the second is that smokers are more reluctant to seek medical attention despite recurrent angina.…”
Section: Discussionsupporting
confidence: 72%
“…25 They were also found to have higher FIGURE 4 Multivariable analysis of restenosis and in -stent thrombosis predictors in patients with a history of percutaneous coronary intervention (PCI) who were referred for PCI on admission; A -predictors of in -stent thrombosis; B -predictors of restenosis Abbreviations: see conflicting results. [29][30][31][32] Similar results were described in patients with restenosis after carotid artery stenting. 33 One of the possible explanations is that smokers have a reduced sensitivity to restenosis, and the second is that smokers are more reluctant to seek medical attention despite recurrent angina.…”
Section: Discussionsupporting
confidence: 72%
“…Our previous clinical follow-up study demonstrated that diabetes remains an independent risk factor for restenosis following DES in coronary arteries (6). There is also evidence that the efficacy of DES in the diabetic state varied with the type of stent (everolimus eluting stents and sirolimus eluting stents > paclitaxel eluting stents and zotarolimus eluting stents) (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the rate of restenosis remains at 7-16% in diabetic patients who have received DES (5). Our previous study demonstrated that diabetes increases restenosis following rapamycin-eluting stent placement (6), indicating that diabetes remains an important predictor for restenosis in the DES era. When rapamycin becomes less effective at preventing in-stent restenosis, this condition is termed 'rapamycin resistance' (6).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the past, in-stent restenosis (ISR) after bare-metal stent (BMS) implantation is thought to be clinically benign. Recently this notion remains controversial and several studies shows a correlation between ISR of BMS, repeated ACS, ischemic relapses and worse longterm clinical outcomes (10,11,12).…”
Section: Discussionmentioning
confidence: 99%